2009
DOI: 10.1146/annurev-polisci-100608-104510
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Government: What You Get

Abstract: In development policy, international organizations have shifted their focus to the importance of good governance and sound institutions. The theory behind this is that only with a high quality of government (QoG) can a country reap the benefits of economic growth and social development. We review the research behind this policy shift and offer a first benchmark statistical analysis. The first section contains a review of the conceptual discussion of what QoG means. Second, we present four salient approaches pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(193 citation statements)
references
References 73 publications
6
180
2
5
Order By: Relevance
“…Quality of government (Holmberg, Rothstein, & Nasiritousi, 2009) and specifically 'good governance within each country' is vital in aiding development and fostering economic growth (United Nations, 2000:13). Given that institutions provide the context within which the firm's transactions take place, it is to be expected that a number of scholars have noted the importance of positive and robust host government institutions (Henisz, 2000;Meyer, 2001).…”
Section: Juridical Institutions and Reinvestmentmentioning
confidence: 99%
“…Quality of government (Holmberg, Rothstein, & Nasiritousi, 2009) and specifically 'good governance within each country' is vital in aiding development and fostering economic growth (United Nations, 2000:13). Given that institutions provide the context within which the firm's transactions take place, it is to be expected that a number of scholars have noted the importance of positive and robust host government institutions (Henisz, 2000;Meyer, 2001).…”
Section: Juridical Institutions and Reinvestmentmentioning
confidence: 99%
“…For example, Holmberg et al suggest a parallel approach to the complex relationship between quality of government and economic growth [51] they claim that although significant relationships can be found between QoG and economic growth, care should be taken in interpreting these results. They suggest that one interpretation of the result could be that the causality between economic growth and QoG resembles a "virtuous circle" in which feedback mechanisms play an important role.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…There is a long list of explanations for corruption levels and the quality of public institutions resorting to differences in cultural values, economic development or political institutions (for an overview see Holmberg, Rothstein & Nasiritousi 2009). In the empirical section we will include one indicator from each of these as control variables.…”
Section: The Bureaucratic Dinosaur Is Backmentioning
confidence: 99%
“…This is not only true for developing countries in Latin America, Africa and Asia, but also for many European democracies such as Italy and Greece (for an overview see Holmberg, Rothstein & Nasiritousi 2009). In the academic field of Public Administration and in national debates in several countries it has been suggested that corruption can be curbed by fostering a traditional organization of public administration, guaranteeing lifelong careers, formalizing recruitments, and introducing strong legal protection for civil servants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation